Dyslipidemia and Conventional Risk Factors in Patients with Acute Coronary Syndrome Admitted in a CCU of a Tertiary Care Hospital of Bangladesh (Cardiovascular Journal, 2021)
Background: Coronary artery disease (CAD) is the single largest cause of death in the developed countries and is one of the leading causes of disease burden in developing countries. The prevalence of dyslipidemia and conventional risk factors profile at the time of admission in patients with Acute Coronary Syndrome (ACS) is not well described in our context. The aim of this study was to investigate the prevalence of dyslipidemia and conventional risk factors profiles of patients with ACS in a tertiary care center of Bangladesh.Methods: This descriptive cross-sectional study included 96 admitted patients of ACS [30 cases of Unstable Angina, 25 cases of Non ST segment Elevation Myocardial Infarction and 41 cases of ST segment Elevation Myocardial Infarction] from the Department of Cardiology, Abdul Malek Ukil Medical College Hospital, Noakhali, Bangladesh from January 2019 to June 2019. Fasting serum lipid profile was obtained within 24 hours of hospitalization and demographic and other cardiovascular risk factors were documented.Results: The mean age of the subjects were 57.7±14.4 years with majority (71.9%) being male. The most frequent reported risk factor was smoking, present in 55.2% of patients, followed by hypertension (47.9%), diabetes (37.5%), dyslipidemia (27.1%) and family history of CAD (15.6%). Based on Body Mass index 50% patients were obese (≥25kg/m2) and 69.8% had central obesity based on waist circumference. The lipid profile analysis revealed that 99% of patients had some type of dyslipidemia, and the most frequent was high level of triglyceride and low levels of high-density lipoprotein cholesterol (68.8% of cases in each).Conclusion: Dyslipidemia is a significant risk factor in patients with ACS and high TG and low HDL-C were more prevalent. Careful attention to its management may help to reduce further events.Cardiovasc j 2021; 14(1): 24-29